TINGGINYA ANGKA PUTUS SEKOLAH DI LOMBOK TIMUR DISEBABKAN OLEH KURANGNYA AKSESIBILITAS PENDIDIKAN BERKUALITAS, TERUTAMA DI PEDESAAN YANG JAUH DARI PUSAT-PUSAT PENDIDIKAN - Saleh, Fatri; Rejeki, Sri; Maemunah, Maemunah (Idaarah: Jurnal Manajemen Pendidikan, 2024)
The aim of this research is to analyze the potential for students to drop out of school in East Lombok based on education and gender. This research uses qualitative research methods because the data studied is the result of observations, interviews and documents. The importance of this research is that it uses qualitative research, so that the results provided explain the problem of out-of-school children in more detail and reality. By including analytical descriptive methods, the aim is to provide visual information about the phenomena we use as research material and compare them with existing data in the field. The results state that factors such as learning motivation, interests and talents, school safety, climate environment, social problems, relationships, violence and economics contribute to the high school dropout rate in East Lombok. Even though the Smart Indonesia Card Program is implemented, factors such as learning motivation, interests and talents, and the environment remain the main causes of school dropout in East Lombok. There are no gender equality problems related to potential school dropouts.